Chinese herbal medicine-derived extracellular vesicles as novel biotherapeutic tools: present and future - Jinying Zhang; Shuo Tian; Lin Guo; Hui Zhao; Zhiguo Mao; Mingsan Miao (Journal of Translational Medicine)
Abstract Extracellular vesicles (EVs) are phospholipid bilayer-enclosed biological particles that are secreted by almost all living cells including animals, plants, and microorganisms. Chinese herbal medicines (CHM) have a long history of using plant-based remedies to treat and prevent human diseases. Chinese herbal medicine-derived extracellular vesicle (CHMEV) generic term refers to nanoscale membrane structures isolated from medicinal plants such as ginseng, ginger, and Panax notoginseng. In recent years, CHMEVs have garnered substantial attention as a novel class of functional components due to their high bioavailability, safety, easy accessibility, and diverse therapeutic effects, indicating their great potential for development as a new dosage form of CHM. Research on CHMEVs in traditional Chinese medicine (TCM) has become a prominent area of interest, opening new avenues for further exploration into the therapeutic effects and functional mechanisms of CHM. Nonetheless, as an emerging field, there is much unknown about these vesicles, and current research remains inconsistent. The review comprehensively summarizes the biogenesis, isolation methods, and physical, and biochemical characterizations of CHMEVs. Additionally, we highlight their biomedical applications as therapeutic agents and drug delivery carriers, including anti-inflammatory, anticancer, regenerative, and antiaging activities. Finally, we propose current challenges and future perspectives. By summarizing the existing literature, we aim to offer valuable clues and inspiration for future CHMEV research, thereby facilitating research standardization of CHMEVs in the treatment of human diseases and drug discovery.